Constitution of the Federal Republic of Nigeria - Federal republic of Nigeria (Lagos, Nigeria : Woye Printers and Publishers, 1981)
The book contains the Constitution of the Federal Republic of Nigeria (Promulgation) decree 1989
Decree 1989 No.12
osa; 08/05/18
Ref.
Keywords: Constitutions; Constitutional law; Constitution - Nigeria